Hubungan Tingkat Pendidikan dan Pengetahuan Dengan Sikap Ibu Terhadap Skrining Hipotiriod Kongenital (SHK) Di BKMIA Kartini Purwokerto - Gus Deriyatno; Made Sumarwati; Galih Noor Alivian (Journal of Bionursing, 2019)
Background: The number of SHK is only a small number, there are probably factors that influence it. It is important to conduct research which can become the basic data for further research. Objective: To determine the relationship between education level and knowledge with maternal attitudes toward congenital hypothyroid screening. Methodology: This study used a cross sectional design method approach. The sampling technique was purposive sampling amounted to 46 respondents. The statistical test used Somers'D correlative. Results: Based on the characteristics, the majority of respondents had an elementary / junior high school level of 45.6% (21 people), medium knowledge was 45.6 (21 people) and had a sufficient attitude of 6.96% (32 people). The correlative test results of the relationship between the level of education and maternal attitudes towards SHK was obtained r=0,287 and p=0.057, the relationship between knowledge and maternal attitudes toward SHK resulted r=0,400 and  p=0.005. Conclusion: The level of education is not related  with maternal attitudes towards SHK but knowledge has a positive correlation with the mother's attitude towards SHK.